2002
DOI: 10.1017/s1472928802000353
|View full text |Cite
|
Sign up to set email alerts
|

Axonal collateralization in primate basal ganglia and related thalamic nuclei

Abstract: This paper provides an overview of the major organizational features of the basal ganglia and related thalamic centers, as delineated by the application of single-axon or single-cell labeling procedures in primates. These studies have revealed that the striatum, the external pallidum and the subthalamic nucleus harbor several types of projection neurons endowed with a highly collateralized axon that allows these neurons to interact with most components of the basal ganglia. In contrast, the internal pallidum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…CM ϭ centromedian nucleus of thalamus; CMA ϭ cingulate motor area; DCN ϭ deep cerebellar nuclei; GPe ϭ globus pallidus pars externa; GPi ϭ globus pallidus pars interna; M1 ϭ primary motor cortex; Pf ϭ parafascicular nucleus of thalamus; PMC ϭ premotor cortex; PN ϭ pontine nuclei; PPNc ϭ pedunculopontine nucleus pars compacta; PPNd ϭ pedunculopontine nucleus pars dissipatus; RTh ϭ reticular nucleus of thalamus; SMA ϭ supplementary motor cortex; SNc ϭ substantia nigra pars compacta; SNr ϭ substantia nigra pars reticulata; STN ϭ subthalamic nucleus; VA ϭ ventroanterior thalamus; Vim ϭ ventral intermediate nucleus of thalamus; VL ϭ ventrolateral thalamus. Figure compiled from data in Pahapill and Lozano, 81 Parent and Parent 168 , and Alexander et al 169 several minutes before, during, and after HFS with parameters (100 A amplitude, 130 Hz frequency, and 60 s pulse width) that improved contralateral rigidity in parkinsonian monkeys. In that study, therapeutic stimulation decreased the mean firing rate in the majority of STN neurons, from 19 Hz to 8 Hz.…”
Section: Somatic Activity In the Stimulated Nucleusmentioning
confidence: 99%
“…CM ϭ centromedian nucleus of thalamus; CMA ϭ cingulate motor area; DCN ϭ deep cerebellar nuclei; GPe ϭ globus pallidus pars externa; GPi ϭ globus pallidus pars interna; M1 ϭ primary motor cortex; Pf ϭ parafascicular nucleus of thalamus; PMC ϭ premotor cortex; PN ϭ pontine nuclei; PPNc ϭ pedunculopontine nucleus pars compacta; PPNd ϭ pedunculopontine nucleus pars dissipatus; RTh ϭ reticular nucleus of thalamus; SMA ϭ supplementary motor cortex; SNc ϭ substantia nigra pars compacta; SNr ϭ substantia nigra pars reticulata; STN ϭ subthalamic nucleus; VA ϭ ventroanterior thalamus; Vim ϭ ventral intermediate nucleus of thalamus; VL ϭ ventrolateral thalamus. Figure compiled from data in Pahapill and Lozano, 81 Parent and Parent 168 , and Alexander et al 169 several minutes before, during, and after HFS with parameters (100 A amplitude, 130 Hz frequency, and 60 s pulse width) that improved contralateral rigidity in parkinsonian monkeys. In that study, therapeutic stimulation decreased the mean firing rate in the majority of STN neurons, from 19 Hz to 8 Hz.…”
Section: Somatic Activity In the Stimulated Nucleusmentioning
confidence: 99%
“…This thalamic complex is composed of at least three types of neurons with different axonal branching patterns that allow this brain center to influence its different target sites in a highly specific manner. Our previous single-axon tracing studies have shown that virtually all components of primate basal ganglia are composed of different types of neurons endowed with a highly collateralized axon (see reviews by Parent et al, 2000, andParent, 2002). By virtue of its highly patterned efferent projection system, the CM/Pf complex should be considered as an integral part of this widely distributed neuronal system.…”
Section: Functional Considerationsmentioning
confidence: 99%
“…The GABAergic GP med projection neurons send their axons to the ventral tier thalamic nuclei and to the PPN; some of these GP med "motor" neurons additionally project to the CM/Pf thalamic complex [27]. The axons of other GP med neurons, termed "limbic" neurons by Parent and Parent (2002), arborize principally within the lateral habenular nucleus (LHb) with some collaterals to the anterior thalamic nuclei.…”
Section: Diversity Of Effects Of Hfs In the Gp Medmentioning
confidence: 99%
“…The axons of other GP med neurons, termed "limbic" neurons by Parent and Parent (2002), arborize principally within the lateral habenular nucleus (LHb) with some collaterals to the anterior thalamic nuclei. Afferents to the GP med include the GABAergic direct striato-pallidal monosynaptic pathway and the glutamatergic subthalamo-pallidal part of the indirect polysynaptic pathway.…”
Section: Diversity Of Effects Of Hfs In the Gp Medmentioning
confidence: 99%
See 1 more Smart Citation